Refugium of nemoral plant relicts of in the valley of the river Belokurikha (Altai) - Revyakina, N. V.; Kozireva, J. V (Проблемы ботаники Южной Сибири и Монголии, 2019)
Nemoral plant relicts in the flora of the Belokurikha river’s valley were identified. The upper reaches of thevalley include 48 % of the relics of the Tertiary flora recorded in the region. Two new species Serratula coronata, Leersiaoryzoides are suggested to be included in the list of nemoral plant relicts.